Evaluation of Trypsin Inhibitor Unit Level with or without the Addition of Protease and an In-feed Acidifier on Nursery Pig Growth Performance, Fecal Dry Matter, and Nutrient Digestibility - Sierra M. Collier; Skyler D. Ward; Katelyn N. Gaffield; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Hari B. Krishnan; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 360 barrows (DNA 200 × 400; initially 12.9 ± 0.59 lb) were used in a 40-d growth trial to evaluate the effects of increasing trypsin inhibitor with or without the addition of protease and benzoic acid on nursery pig growth performance, fecal dry matter, and nutrient digestibility. Pigs were weaned at approximately 21 d of age and randomly allotted to pens. Pens of pigs were blocked by initial BW and allotted to one of eight treatments in a randomized complete block design with five pigs per pen and nine pens per treatment across two barns. The eight treatments were arranged in a 2 × 2 × 2 factorial design with main effects of trypsin inhibitor (1.4 or 2.8 TIU/mg of complete feed), protease (none or 50 mg/kg ProAct 360), and benzoic acid (none or 0.5% VevoVitall). Soy flour (80 TIU/mg) was added at the expense of soybean meal (7 TIU/mg) to create the 1.4 or 2.8 TIU/mg of complete feed levels. Diet formulation was based on analyzed nutrient values of the soy flour and soybean meal, assuming digestibility coefficients for soy flour equivalent to those of soybean meal. Experimental diets were fed in three phases: phase 1 from d 0 to 10, phase 2 from d 10 to 24, and phase 3 from d 24 to 40. Feces were collected from three pigs per pen on d 10 and 40 to determine fecal DM, and d 40 fecal samples were used to determine apparent total tract digestibility (ATTD) of DM and CP. The main effect of TIU negatively impacted (P ≤ 0.014) growth performance in all phases, while the main effect of acidifier tended (P ≤ 0.089) to improve ADG and F/G in phase 3. No significant main effects of protease in the phases were observed. Overall, from d 0 to 40, there was a three-way interaction observed (P = 0.024) where in low TIU diets, pigs fed diets with either acidifier or protease had numerically lower ADG compared to the low TIU control and the low TIU diet with both acidifier and protease. However, in high TIU diets, pigs fed either acidifier or protease had greater ADG compared to the high TIU control diet without any additive and the high TIU diet with both acidifier and protease. A similar TIU × protease × acidifier interaction was marginally significant for ADFI (P = 0.054). Pigs fed diets with 2.8 TIU/mg of complete feed had increased d 10 fecal DM; however, there were no differences on d 40. For the ATTD of DM and CP, there was an interaction (P = 0.028) between TIU and acid, where pigs fed the acidifier had improved ATTD compared to pigs fed no acid in a diet containing 1.4 TIU/mg of complete feed; however, pigs fed 2.8 TIU/mg of complete feed had similar ATTD regardless of acid inclusion. For overall main effects, increased TIU worsened (P < 0.05) ADG, ADFI, and F/G; protease tended to worsen (P = 0.067) F/G; and acidifier had no effects on growth performance. This study suggests that increased dietary TIU negatively affects nursery pig performance, but the inclusion of either a protease or benzoic acid may help mitigate a portion of the effect of high TIU, even as low as 2.8 TIU/mg of complete feed.
Keywords: benzoic acid; protease; soybean meal; trypsin inhibitor; weanling pigs